2010
DOI: 10.1089/ten.tea.2009.0798
|View full text |Cite
|
Sign up to set email alerts
|

Photocrosslinkable Hyaluronan-Gelatin Hydrogels for Two-Step Bioprinting

Abstract: Bioprinting by the codeposition of cells and biomaterials is constrained by the availability of printable materials. Herein we describe a novel macromonomer, a new two-step photocrosslinking strategy, and the use of a simple rapid prototyping system to print a proof-of-concept tubular construct. First, we synthesized the methacrylated ethanolamide derivative of gelatin (GE-MA). Second, partial photochemical cocrosslinking of GE-MA with methacrylated hyaluronic acid (HA-MA) gave an extrudable gel-like fluid. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
299
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(309 citation statements)
references
References 49 publications
2
299
0
1
Order By: Relevance
“…The overall results of a mathematical model showed that the conductivity of a metal nanoparticle can be decreased when the particle size is smaller, confirming the experimental results of [10]. By functionalizing nanoparticle surfaces, the interaction between a polymer and nanoparticles can be strengthened [11][12][13]. Various types of metal nanoparticles have been used in the production of nanocomposite hydrogels in the field of biomaterials including gold [14], silver [15] and other noble metal nanoparticles, while metal oxide nanoparticles such as iron oxide [16] and zirconia [17] have also been used.…”
Section: Metal Nanoparticlessupporting
confidence: 73%
“…The overall results of a mathematical model showed that the conductivity of a metal nanoparticle can be decreased when the particle size is smaller, confirming the experimental results of [10]. By functionalizing nanoparticle surfaces, the interaction between a polymer and nanoparticles can be strengthened [11][12][13]. Various types of metal nanoparticles have been used in the production of nanocomposite hydrogels in the field of biomaterials including gold [14], silver [15] and other noble metal nanoparticles, while metal oxide nanoparticles such as iron oxide [16] and zirconia [17] have also been used.…”
Section: Metal Nanoparticlessupporting
confidence: 73%
“…The GelMA was used as bulk matrix to mimic native ECM and also as a cell carrier to encapsulate cells within the matrix (Figure 8). [182] Prestwich and co-workers have reported the combination of thermogelation via gelatin (providing rapid physical gelation once cooled) with UV photopolymerization of pendant methacrylate groups (providing post-reaction stabilization and mechanical enhancement of the printed structure [183] ), while Burdick and co-workers have reported a combination of shear-disruptable host-guest physical interactions (providing rapid gelation once the nozzle shear is relieved) with UV photopolymerization as a 3D printable hydrogel ink capable of supporting cell growth. [184] However, to our knowledge, in situ covalent chemistry has not yet been reported in conjunction with 3D printing, likely attributable to the incompatibility of most current 3D printer designs for enabling the rapid mixing required for printing covalent in situ gelling polymers.…”
Section: Solvent/additive-free Hydrogelsmentioning
confidence: 99%
“…HA forms very soft gels but can be modified and crosslinked using a variety of methods including the UV method described in Section 4.1 [76] and thiol-modified HA using gold nanoparticles [77] to increase its stiffness. Similarly, fibrin is already used in surgery as a haemostatic agent and sealant [78,79] .…”
Section: Natural Materialsmentioning
confidence: 99%